2011
DOI: 10.3168/jds.2010-3649
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the prolactin-release inhibitor quinagolide on lactating dairy cows

Abstract: In most mammals, prolactin (PRL) is essential for maintaining lactation, and yet the short-term suppression of PRL during established lactation by bromocriptine has produced inconsistent effects on milk yield in cows and goats. To assess the effect of the long-term inhibition of PRL release in lactating dairy cows, 5 Holstein cows in early lactation received daily intramuscular injections of 1mg of the PRL-release inhibitor quinagolide for 9 wk. Four control cows received the vehicle (water) only. During the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 43 publications
6
66
2
2
Order By: Relevance
“…The effect of melatonin would be expected to reduce both basal and milking-induced increases in PRL, although that remains to be confirmed experimentally. In a recent study, quinagolide, a PRLrelease inhibitor, was administered to lactating cows for approximately 8 wk to examine the effect of decreased PRL on milk yield (Laçasse et al, 2011). After 4 wk, quinagolide-treated cows produced less milk compared with controls that received vehicle.…”
Section: Photoperiod and Lactationmentioning
confidence: 98%
“…The effect of melatonin would be expected to reduce both basal and milking-induced increases in PRL, although that remains to be confirmed experimentally. In a recent study, quinagolide, a PRLrelease inhibitor, was administered to lactating cows for approximately 8 wk to examine the effect of decreased PRL on milk yield (Laçasse et al, 2011). After 4 wk, quinagolide-treated cows produced less milk compared with controls that received vehicle.…”
Section: Photoperiod and Lactationmentioning
confidence: 98%
“…Although it has been well established in rodents and lagomorphs that PRL depletion reduces milk production, in ruminants the effects of PRL inhibition are less obvious, and the galactopoietic role of PRL has been a matter of debate for several decades (Knight, 2001). Several of the present authors recently showed that the long-term inhibition of PRL with a potent dopamine agonist, namely quinagolide (QN), reduced milk yield in dairy cows (Lacasse et al, 2011). However, a complete demonstration of the galactopoietic role of In vivo inhibition followed by exogenous supplementation demonstrates galactopoietic effects of prolactin on mammary tissue and milk production in dairy cows V. Lollivier,* † ‡ P. Lacasse, § J. Angulo Arizala,# P. Lamberton,* † S. Wiart,* † J. Portanguen,* † R. Bruckmaier,‖ and M. Boutinaud* † 1 PRL in ruminants requires showing that the effect of QN on the mammary gland is due to the inhibition of PRL secretion.…”
Section: Introductionmentioning
confidence: 96%
“…Plasma was separated by centrifugation at 4°C and 3,000 g for 15 min and then stored at Ϫ20°C for subsequent analysis. Plasma PRL concentrations were measured with an indirect competitive ELISA (31). Intra-assay variability was Ͻ2%, and inter-assay variability was Ͻ12%.…”
Section: Methodsmentioning
confidence: 99%